Academic Participation of Female Students in Biology: A Primary School Study from Western Hararghe, Ethiopia - Eba, Wondimagegn Wolde; Tensaw, Mokonin; Atle, Daniel; Tahir, Muhidin (Lia Center of Research and Education, 2026)
In Ethiopia, the enrollment of females in school is still lower than that of males. Women also struggle greatly in Dabia Primary School to participate in the educational process. this study aims to identify the factors that influence the academic achievement of grade eight female students at Dabia Primary School. A cros sectional study was conducted from to, may 30 to July 01, 2024 on 53 respondents in all, including 36 female students in grade 8 and 17 teachers, were sampled for this study. The students were selected employing simple random selection techniques, while teachers were chosen via purposive sampling. The primary instruments for acquiring data were interviews and questionnaires. Frequency counts, percentages, and mean values were used to examine the data. The study's findings showed that psychological elements (96%) like shyness and concern of what others will think of them were highly rated by both teachers and female pupils. The most detrimental influences were rated as psychological factors (92.5%), sociocultural factors (92.5%), personal factors (53%) such as poor academic backgrounds of students and poor communication skills, and sociocultural factors (92.5%) such as livelihood dependence of the respondents and negative attitudes toward female education and the allocation of household tasks to women.